Native valve, prosthetic valve, and cardiac device-related infective endocarditis: A review and update on current innovative diagnostic and therapeutic strategies - Kouijzer, Joop J. P.; Noordermeer, Daniëlle J.; van Leeuwen, Wouter J.; Verkaik, Nelianne J.; Lattwein, Kirby R. (Frontiers in Cell and Developmental Biology, 2022)
Infective endocarditis (IE) is a life-threatening microbial infection of native and prosthetic heart valves, endocardial surface, and/or indwelling cardiac device. Prevalence of IE is increasing and mortality has not significantly improved despite technological advances. This review provides an updated overview using recent literature on the clinical presentation, diagnosis, imaging, causative pathogens, treatment, and outcomes in native valve, prosthetic valve, and cardiac device-related IE. In addition, the experimental approaches used in IE research to improve the understanding of disease mechanisms and the current diagnostic pipelines are discussed, as well as potential innovative diagnostic and therapeutic strategies. This will ultimately help towards deriving better diagnostic tools and treatments to improve IE patient outcomes.